Measuring economic and institutional integration - Volker Nitsch; Helge Berger (Technische Universität Darmstadt, Department of Law and Economics, 2015)
[Introduction] A quantitative assessment of the level of integration among geographic units (such as regions, states or countries) is of interest to a wide range of audiences. Policy-makers, for instance, may want to identify barriers to cross-regional interaction. José Manuel Barroso (2009, p. 28), the then President of the European Commission, provides an illustrative example; in the political guidelines for his second term as the head of the Commission he notes: “I intend to launch a major analysis of the `missing links' in the internal market, to find out why it has not delivered on its full potential and thereby to identify new sources of growth and social cohesion.” Five years later, but still along similar lines, the European Commission (2013, p. 4) argues: “Today, during the crisis, it is more necessary than ever to address where the single market does not yet function as it should to the benefits of citizens and businesses.” For economists, the measurement of integration is of particular importance when quantifying the gains from exchange. Any reasonable assessment of the consequences of a removal of barriers to trade requires measures (observed or constructed) that allow a comparison of different states of integration. As a result, empirical findings may be sensitive to the exact definition of measures of integration. Rodriguez and Rodrik (2001), for instance, highlight the relevance of measurement issues in an article which has become an instant classic; in a critical review of empirical analyses of the effect of trade openness on economic growth, they illustrate the difficulties in quantifying a country's openness to trade. In this chapter, we review the process of European integration in the post-World War II period and discuss issues related to the measurement of economic and institutional integration. Starting from the observation that the quantitative assessment of the level of integration is a non-trivial task, in Section 2 we highlight the challenges involved in the quantification from a European perspective. In Section 3, we review a selection of available indicators of European integration in more detail. A brief summary concludes the chapter.
Keywords: 330